2023
DOI: 10.1063/5.0126796
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Al doping on dislocation inclinations and strain of GaN films on Si substrates

Abstract: We present how the interaction between Al dopants and threading dislocations affects dislocation inclinations and then plays an important role in controlling residual strain in GaN-on-Si epitaxial films. When the Al concentration in the GaN epitaxial film is increased to 0.85%, the dislocations extend almost in the growth direction, contributing to a strain-free epitaxial film. We suggest that the Al atoms could substitute for Ga vacancies at the dislocation cores on the growth surface and then inhibit the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The reason for this is that the recent theoretical calculations have shown that the concentration of tri-carbon complexes exceeds that of C N at C doping concentrations higher than ∼10 18 cm −3 . 31) In addition, the C N -C Ga -C N complexes explained by the DFT calculations have been reported to exhibit behavior similar to that of the isolated C N acceptor, with transition levels of ∼0.55 eV. 22,28) Although our experimental carrier trap level is not in agreement with the calculated one, it is relatively close to that of the C N -C Ga -C N complexes compared to other tri-carbon complexes that have deeper transition levels above 1 eV.…”
Section: Resultsmentioning
confidence: 99%
“…The reason for this is that the recent theoretical calculations have shown that the concentration of tri-carbon complexes exceeds that of C N at C doping concentrations higher than ∼10 18 cm −3 . 31) In addition, the C N -C Ga -C N complexes explained by the DFT calculations have been reported to exhibit behavior similar to that of the isolated C N acceptor, with transition levels of ∼0.55 eV. 22,28) Although our experimental carrier trap level is not in agreement with the calculated one, it is relatively close to that of the C N -C Ga -C N complexes compared to other tri-carbon complexes that have deeper transition levels above 1 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Eventually, the length of the bent segment of the TDs becomes equal to the length of the misfit segment, leading to a decrease in the elastic strain energy and, therefore, a reduction in dislocations, resulting in a higher crystalline quality. While the use of strain has been utilized by many researchers to reduce dislocations, it is important to note that the strain profile should be chosen wisely. When compared to a sharp strain boundary, a linear strain gradient offers TDs the opportunity to reduce the energy of the system more by leaving the system than by propagating into the strained region.…”
Section: Resultsmentioning
confidence: 99%